Spectroscopic properties of explosive volcanism within the Caloris basin with MESSENGER observations. Issue 12 (2nd December 2015) - Besse, S.; Doressoundiram, A.; Benkhoff, J.
Abstract: Volcanism on Mercury has been indisputably identified at various locations on the surface, by means of both effusive and explosive volcanism. Its characterization is crucial to understand the evolution of the planet, in particular the thermal evolution of the mantle, and the volatile content of the planet. This analysis presents a detailed view of the pyroclastic deposits of the Caloris basin. Observations from the Mercury Atmospheric and Surface Composition Spectrometer (MASCS) are used to understand the spectral characteristics of the pyroclastic deposits, both in the visible and near‐infrared. Additional calibration steps are proposed to reconcile the difference of absolute reflectance between the visible (VIS) and near‐infrared (NIR) detectors. These calibration steps allow the use of the full spectral range of the MASCS instrument. Pyroclastic deposits exhibit a redder spectral slope in the VIS and NIR. This spectral slope diminishes toward the edge of the deposits to match that of Mercury's average surface. Spectral properties in the ultraviolet (UV) also change as a function of distance to the vent. Only the UV properties unambiguously separate the pyroclastic deposits from Mercury's average spectra. The spectral variations are consistent with a lower iron content of the pyroclastic deposits with respect to the average surface of Mercury, similar to what has been proposed for pyrolcastic deposits on the lunar surface. Nonetheless, given the limited illumination conditions diversity of the MASCS instrument, other causes such as grain size, space weathering, and bulk composition could also be accounted for the spectral variations. Variability of the pyroclastic deposits' properties within the entire basin are potentially identified between the three main clusters, and could be related to space weathering of deposits of different ages. Key Points: The VIS and NIR spectra are reconciled to use spectra from 300 nm to 1450 nm Pyroclastic deposits have different spectral properties from Mercury average Spectral properties are consistent with a low iron content or a change in grain size